Virtual Reality In Web-Based Application : The UUM Sports Complex - Juliana, Abu Bakar (2002)
This research aims to study how VR can deploy a low-cost but high in performance Web-based virtual tour system by using VR techniques, namely, CAD and VRML modelling and panoramic imaging. This research adapts Systems Development Research methodology to achieve its aim. This methodology includes the construction of the research conceptual framework, the system architecture development, the system analysis and design, the prototype system development, the system performance evaluation. Along the way to solve the research questions, this research has compared the characteristics of the VR authoring tools and also discovered the design issues during the prototype development activity. The output of this research is the Universiti Utara Malaysia (UUM) Sports Complex Virtual Tour Website, enriched with interactivity and able to represent the real physical environment. The design frameworks for VR techniques in creating the virtual tour system were established based on the prototype development experience. This thesis also can hopefully be guidelines to Web developers for web-based virtual tour system construction.